Rapid and sensitive detection of Hg2+ with a SERS-enhanced lateral flow strip. Issue 19 (30th August 2022) - Yao, Li; Chen, Yunlin; Wang, Ranran; Yan, Chao; Xu, Jianguo; Yao, Bangben; Cheng, Jigui; Chen, Wei
Abstract : A SERS-LFS strategy was designed and applied for the direct detection of target Hg 2+ with greatly improved sensing performance by SERS measurements on the T line of the LFS, which did not change the intrinsic simplicity of the LFS. Abstract : Mercury ions are some of the most toxic heavy metal ions widely distributed in the environment. Hg 2+ cannot be degraded by microorganisms and can accumulate in the body through the food chain, posing a great threat to human health. Herein, a method combining surface-enhanced Raman scattering (SERS) with a lateral flow strip (LFS) (SERS-LFS) was developed for the rapid and quantitative analysis of Hg 2+ . The recognition of Hg 2+ by the LFS depends on a specific T–Hg–T strategy. Rhodamine 6G (R6G), as a SERS reporter, was assembled on the surface of Au@Ag core–shell nanoparticles, which served as an effective SERS substrate on both the T and C lines of the LFS. Using this SERS-LFS, the presence of target Hg 2+ could be measured through the appearance of an orange color on the T line of the LFS. Furthermore, with the direct measurement of SERS on the T lines of the LFS, the SERS signal could be collected even at a low concentration of Hg 2+, at which point the signal on the T lines could not be observed. Based on the intensities of the characteristic peak at 1513 cm −1 of R6G collected on the T lines of the LFS, a linear relationship was obtained in the range of 0.01 nM to 1 nM, and the detection limit of the LFS was greatly improved by at least 20 times over the colorimetric results of the traditional LFS based on naked-eye observation. More importantly, this SERS-LFS did not affect the intrinsic simplicity of the LFS. This developed SERS-LFS holds great potential in practical routine screening in food safety and environmental monitoring.